The Relationship between Pathological Features and 18F-FDG PET/CT that Changed the Surgeon's Decision as Neoadjuvant Therapy in Breast Cancer - Edizsoy, Akay; Dağ, Ahmet; Özcan, Pınar Pelin; Koç, Zehra Pınar (World Journal of Nuclear Medicine, 2022)
Objective Patients diagnosed with breast cancer and decided to undergo surgical treatment can undergo neoadjuvant therapy following their 2-deoxy-2-[fluorine-18]fluoro-D-glucose positron emission tomography/computed tomography (18F-FDG PET/CT) findings. The present study aims to determine the statistical significance of these patients whose treatment plan was changed and the reasons for the change in the plan.Materials and Methods The demographic features and treatment plans of 151 cases who were diagnosed with any stage of breast cancer were evaluated. These patients consist of those who admitted to Mersin University Hospital Breast Outpatient Clinic between January 2016 and December 2019. All of these patients aged between 41 and 85 years were examined with 18F-FDG PET/CT after the decision for surgical treatment is made. The analysis included tumor pathology, side, type, subtype, size, and centricity in this study.Results About 18.5% (n = 28) of patients' treatment plan was changed after 18F-FDG PET/CT. They received neoadjuvant therapy. About 81.5% (n = 123) of patients did not receive neoadjuvant therapy. Significant differences were observed between patients changed treatment plan and not changed concerning age, lymph node involvement, tumor size, centricity, and subtypes parameters.Conclusion Conventional imaging examinations are used in patients with breast cancer. These examinations may not be sufficient to determine advanced disease requiring neoadjuvant treatment. With 18F-FDG PET/CT examination, these advanced stage patients are not overlooked. In our study, approximately one in five patients, treatment plan changed after 18F-FDG PET/CT examination.
Keywords: breast cancer; PET; subtype; neoadjuvant